Trends and patterns in food consumption and nutrition of rural and urban poor in Bangladesh, 1991-2000 - Yusuf, Harun K.M. (BRAC Research and Evaluation Division (RED), 2019)
A review report is prepared on the trends and patterns of food intake and nutritional status of the poor rural and urban households of Bangladesh during the decade of 1991-2000. Because agricultural production is the main determinant of the quantity and quality of meals in a poor agrarian country like Bangladesh, a thorough review of trends in gross production and gross per capita availability of commonly consumed foods was first made. The decade is marked by a commendable increase in food production, particularly rice during the second half of the decade, along with other food items like wheat, potato, vegetables, fish, meat and milk. This made the average national diet of the year 2000 richer in terms of quantity (892 g/capita/day), energy (2,112) Kcal and protein (53 g) compared to the diet of all previous survey years. However, the country is yet to acieve the desirable requirement level in any terms: the diet is still highly imbalanced, with rice and other cereals contributing nearly 80% of total energy and fruits and vegetables contributing only 3%. The diet is thus deficient in vitamins and minerals. The decade of 1991-2000 is marked by a commendable economic growth, with concomitant decline in the incidence of both absolute poverty and extreme poverty, by 9 percentage points each, more in urban than in rural areas, although the rate of decline in urban poverty slowed down in the latter years of the decade. However, in 2000, the incidence of absolute poverty was still 50% and the incidence of extreme poverty was 34%. In absolute terms, during the decade, the number of poor in rural areas decreased from 58 million to 42 million, while the number of poor in urban areas showed an appalling 100% increase from 7 million to 15 million. Since food distribution inequity is heavily weighted on the poor, the food intake of the poor in both rural and urban areas, remained inadequate in quantity (around 700 g/day), energy (1790 Kcal, 25% less than the requirement) as well as in protein (40 g/day, 30% less than required). Their diet is also precariously imbalanced, nearly 90% energy coming from cereals, 85% from rice alone, an inevitable consequence of which is malnutrition. Analysis shows that between 1991-2000, no improvement had occurred in the quantity nor in the quality of the diet of the poor and the poorest (bottom 40% expenditure category). This is true for both rural and urban areas. The urban slums are even worse. In poor households of both rural and urban areas, allocation of household expenditure for food is 70%. So, more than two-thirds of the income is spent for food which is inadequate in quantity and quality. Needless to say, the remaining 30% can barely meet the other necessities of life. Market dependence is very high in the rural areas, where nearly one-quarter of major foods like rice, vegetables and fish are procured from own production and the remainder is purchased from the market. Only in case of egg, the proportion of own production in both poor and rich households is 32-54%, indicating traditional poultry raising in rural areas. Parallel with national average economic growth, poverty reduction, increased food production and food intake. Bangladesh has achieved a commendable reduction in child malnutrition rates during the nineties. Night blindness due to vitamin A deficiency in children under 6 years of age decreased to almost nonexistence levels (0.3%) during the decade. But despite these improvements. 50% of preschool children were still stunted or underweight. 18-19% severely. in 2000. Percentage of malnourished children coming from poor families is even higher. over 60%. The prevalence is higher in rural than in urban areas and girls are more affected than boys. Over 50% children are anaemic. Chronic energy deficiency (CED) prevalence in women of child bearing age has also decreased over the years of the decade. but still. 45% of rural and 35% of urban (slum) mothers suffer from CED. Still. about half of all pregnant mothers are anaemic. Infant feeding practice (colostrum and breast milk as first food after birth and start of complementary feeding with right type of food at the right time, i.e. 5 months of age or later) are found to have strong bearing on child's nutritional status. Enriching the family food, which becomes more and more important in the infant's diet, may be enriched with egg, fish, pulse and oil. Appalling is the finding that 65% of poor families do not eat egg at all, even though they have egg in the house: they save it for hatching or sell it for hard cash. Thus, poor households, rural and urban alike, did not get the benefit of increased food production and the economic growth that the country has achieved during the nineties: in year 2000, their food intake was low and their food was imbalanced , as it was in year 1991. Those who have come out of poverty are lucky, but more pro-poor action programmes need to be taken to bring more poor out of poverty, and sooner the better.